Majcnova kratka proza v kontekstu moderne in njene slogovne značilnosti - Čeh Steger, Jožica (Slavistična revija, 2006)
The article treats Majcen's short prose untill 1923, the main portion of which the author wrote during his student years in Vienna, i.e., between 1908 and 1913. The analysis of Majcen's short prose is placed in the context of Ivan Cankar and the Vienna Moderna. The image of a childish woman, the conflict between genders, the topic of an artist and a woman, stylized descriptions of girls, death, and literary spaces connect Majcen's short prose with Peter Altenberg and the motifs, thematic, and stylistic elements of Art Nouveau (Vienna Secession).
Keywords: bourgeois prose; eroticism; erotika; female characters; female types; kratka proza; Majcen, Stanko; meščanska proza; metropolitan eroticism; moderna; Moderna Therapeutics; prose; proza; short prose; slog; Slovene literature; slovenska književnost; style; velemestna erotika; ženski liki